2011
DOI: 10.1002/pca.1332
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Identification of Calotropagenin Glycosides Using High‐Performance Liquid Chromatography Electrospray Ionisation Tandem Mass Spectrometry

Abstract: High performance liquid chromatography in combination with electrospray ionization tandem mass spectrometry involving metal cationisation by post column addition of alkali salts was successfully utilised for the rapid identification of calotropagenin glycosides/derivatives in Calotropis procera extract.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 37 publications
2
11
0
Order By: Relevance
“…The tandem mass spectrum showed daughter ions at m/z 387, 359, 351, 334 and 323 (Fig. 7), which was accordant with the specific MS/MS spectra of calotropagenin (Kanojiya and Madhusudanan 2011). The result suggested that some of cardenolides in C. gigantea hairy root cultures are derivatives of calotropagenin.…”
Section: Effects Of Elicitation With Mj Ye and Cssupporting
confidence: 84%
“…The tandem mass spectrum showed daughter ions at m/z 387, 359, 351, 334 and 323 (Fig. 7), which was accordant with the specific MS/MS spectra of calotropagenin (Kanojiya and Madhusudanan 2011). The result suggested that some of cardenolides in C. gigantea hairy root cultures are derivatives of calotropagenin.…”
Section: Effects Of Elicitation With Mj Ye and Cssupporting
confidence: 84%
“…Previously, it was reported that the apical twigs and latex of C. procera produced greatest inhibition zones against S. aureus [32]. Furthermore, we demonstrated the high antimicrobial potency of the C. procera extract against all the tested bacteria may be due to the high content of glycosides and various proteins present in the aqueous extracts [23, 24]. The differences in the antimicrobial activity of various extracts may be directly related to the diversity of compounds accumulated in C. procera : proteins [21], calotropagenin glycosides [23], cardenolides, flavonoids, and saponins [24] thus corroborating our results.…”
Section: Discussionsupporting
confidence: 51%
“…Furthermore, we demonstrated the high antimicrobial potency of the C. procera extract against all the tested bacteria may be due to the high content of glycosides and various proteins present in the aqueous extracts [23, 24]. The differences in the antimicrobial activity of various extracts may be directly related to the diversity of compounds accumulated in C. procera : proteins [21], calotropagenin glycosides [23], cardenolides, flavonoids, and saponins [24] thus corroborating our results. Such compounds can bind the Gram-negative bacteria to form a heavy soluble complex on the cell surface that subsequently disturbs the interaction between bacteria and cell receptors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mobile phase consisted of (A) 1:1 (v/v) acetonitrile: methanol and (B) 0.1mM ammonium acetate in water at a flow rate of 1ml/min and injection volume 20µl. The column effluent was detected at 280 nm with an UV detector 9 .…”
Section: Chromatographic Conditionsmentioning
confidence: 99%